2004
DOI: 10.1097/00005176-200405000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Nontyphoid Salmonellosis in Taiwan Children: Clinical Manifestations, Outcome and Antibiotic Resistance

Abstract: Blood culture should be obtained in patients with nontyphoid salmonellosis to detect bacteremia. In treating antibiotic-resistant nontyphoid salmonellosis, antibiotics are still not mandatory for patients who present with primarily gastrointestinal symptoms and limited signs of systemic inflammation reflected by a low severity score (low C-reactive protein, fewer band cells in peripheral blood, and fewer days of fever before admission). Susceptibility data should be promptly obtained because use of discordant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
4
23
1
Order By: Relevance
“…The incidence of coinfection in this study was 5.5%, which is within the ranges reported by previously published studies (0.48e7.4%) [13e15]. It is not surprising that the prevalence of coinfection was higher among males in this study because the prevalences of rotavirus and NTS infection have been reported as higher in male children [12,16]. However, there were no differences between males and females with coinfection or NTS infection in terms of clinical severity score or length of hospitalization.…”
Section: Discussionsupporting
confidence: 88%
“…The incidence of coinfection in this study was 5.5%, which is within the ranges reported by previously published studies (0.48e7.4%) [13e15]. It is not surprising that the prevalence of coinfection was higher among males in this study because the prevalences of rotavirus and NTS infection have been reported as higher in male children [12,16]. However, there were no differences between males and females with coinfection or NTS infection in terms of clinical severity score or length of hospitalization.…”
Section: Discussionsupporting
confidence: 88%
“…Among our Salmonella cases, 70.4% occurred between April and September. These months are warmer and are typically the rainy season in Taiwan [18]. This is consistent with the epidemiology of non-typhoid salmonellae [19].…”
Section: Discussionsupporting
confidence: 75%
“…Most of our patients survived; one with C. septicum infection expired. Compared with previous series of colon perforations, the mortality was influenced by a different etiology [9,18,[25][26][27][28]. C. septicum infection in children is associated with high mortality [26][27][28].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These infections in infants would all seem to have been locally acquired within Denmark with only a single child infant case in 2009 reporting a history of travel. None of the infants in our study developed invasive infections like bacteraemia, meningitis or septic arthritis which can be seen with non-typhoidal Salmonella infections, especially in the developing world [8,9], and none of the children died.…”
Section: Discussionmentioning
confidence: 63%